Analysis of the Main Economic Sectors in the City of Palangka Raya - Fijai Junardi Situmeang; Marhot Siregar; Dedi Takari (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2019)
This study aims to (1) Know the economic sector that is the leading sector in the City ofPalangka Raya, (2) Know the regional economic structure in the City of Palangka Raya, (3)Know the pattern of regional economic growth in the City of Palangka Raya, (4) Know theproduct trends pre-eminent in the City of Palangka Raya, (5) Knowing what policy strategies canbe formulated seen from the strengths, weaknesses, opportunities and threats in the leadingeconomic sector for the development of the City of Palangka Raya. The analysis used is theLocation Quote (LQ) analysis, Shift Share analysis, Klassen Typology analysis, Trend analysis,SWOT analysis. The results of this study indicate that (1) The leading economic sectors inPalangka Raya City from 2010 - 2016 are the Electricity and Gas Procurement sector, theGovernment Administration sector, the Obligatory Social Security and Defense, the Provision ofAccommodation and Food and Beverage sectors, the Financial Services and Insurance sectors,Water Supply sector, Waste Management, Waste and Recycling, Corporate Services sector,Information and Communication sector, Wholesale and Retail Trade sector, Car and MotorcycleRepair sector, Real Estate sector, Transportation and Warehousing sector, Health Services andSocial Activities sector, Other services sector, Construction sector, Education Services sector; (2)The regional economic structure in the City of Palangka Raya with the highest value is theGovernment Administration, Defense and Social Security sector which must be first, theWholesale and Retail Trade sector, Car and Motorcycle Repair in second, the Constructionsector in third, the Financial Services and Insurance sector came in fourth, the Transportation andWarehousing sector in fifth; (3) The pattern of regional economic growth in the City of PalangkaRaya in Quadrant I is the Water Supply, Waste Management, Waste and Recycling sector, theConstruction sector, the Wholesale and Retail Trade sector, the Repair of Cars and Motorcycles,the Provision of Accommodation and Food and Beverage sectors, the sector Information andCommunication, Real Estate sector, Corporate Services sector, Education Services sector, HealthServices sector and Social Activities sector and other Services sectors; Quadrant II is theElectricity and Gas Procurement sector, the Transportation and Warehousing sector, theFinancial Services and Insurance sector and the Government Administration, Defense andMandatory Social Security sectors; Quadrant III are; Quadrant IV is the agriculture forestry andfisheries sector, the mining and quarrying and processing industries sectors.